Representation of the Object of Love in Valerie Patkar’s Novel Logika Asa: An Erich Fromm Psychological Study - Hermila Izza Aliffia; Anas Ahmadi (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the object of love in the novel Logika Asa by Valerie Patkar using Erich Fromm’s theory of love psychology. This research uses a literary psychology approach with a qualitative method, presenting results descriptively. The theory used in this study is Erich Fromm’s love psychology, which focuses on analyzing objects of love in literary works, specifically novels. The data source used is the novel Logika Asa by Valerie Patkar, with research data in the form of quotations. The data collection technique used is the observation technique by reading and noting. The data are analyzed using a descriptive analysis technique by selecting data, categorizing data according to the theory, analyzing data, and describing the data that has been found. The research results show that the novel Logika Asa by Valerie Patkar contains five objects of love according to Erich Fromm’s theory of love, namely: 1) love for others, demonstrated through aspects of care and responsibility, 2) maternal love, demonstrated through aspects of care and responsibility, 3) erotic love, demonstrated through aspects of individual attraction specifically towards an individual and sacrifice, 4) self-love, demonstrated through aspects of responsibility and care for oneself, and 5) love for God, demonstrated through the aspect of feeling His presence in reality and always remembering God in every step. The embodiment of the objects of love from the data found is supported by several elements in the form of a sense of care and a sense of responsibility.